The Legal System of Scotland as a Hybrid Legal System - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2023)
This scientific article analyzes the legal system of Scotland, which, as you know, is not subject to English (common) law. The paper addresses the question of which legal family it is a part of.